Determinação do valor - \'-Q IND.0\' da reação \'ANTPOT.20 NE\' (d, \'ALFA\') \'ANTPOT.18 F\' - Boueres, Luis Carlos Soares (1969)
Determinação do valor - \'-Q IND.0\' da reação \'ANTPOT.20 NE\' (d, \'ALFA\') \'ANTPOT.18 F\'